Albumin nanoparticles are a promising drug delivery system in dentistry - Mohammad Kiarashi; Saman Yasamineh (BioMedical Engineering OnLine)
Abstract Periodontal infection is a long-lasting inflammatory condition caused by the growth and development of an abnormal and harmful community of microorganisms. This destructive illness leads to the loss of the tissues that support the teeth, degradation of the bone surrounding the teeth, and eventually tooth loss. To treat oral infections, it is necessary to use nonsurgical methods such as antibiotics. However, the indiscriminate and incorrect use of antibiotics results in drug resistance. Among these alternate therapeutic options, using nanoparticles to treat infectious dental disease was particularly significant. Consequently, researchers have worked to develop an effective and satisfactory drug delivery method for treating periodontal and dental illnesses. Albumin nanoparticles serve a considerable function as carriers in the drug delivery of chemical and biomolecular medications, such as anticancer treatments; they have several advantages, including biocompatibility and biodegradability, and they are well-tolerated with no adverse effects. Albumin nanoparticles have several benefits over other nanomaterials. Protein nanocarriers provide advantages such as biocompatibility, biodegradability, reduced immunogenicity, and lower cytotoxicity. Furthermore, this nanoparticle demonstrated significant intrinsic antibacterial properties without being loaded with antibiotic medicines. As a medication and antibacterial nanoparticle delivery method, albumin nanoparticles have substantial applications in periodontal and dental infectious disorders such as periodontal infection, apical periodontitis, and peri-implantitis. As a result, in this article, we studied the usage of albumin nanoparticles in dental disorders. Graphical Abstract